Competition warm-up strategies in sub-elite and elite flat-water sprint kayak athletes. Issue 11 (3rd June 2021) - Hogan, Cruz; Binnie, Martyn J.; Doyle, Matthew; Peeling, Peter
ABSTRACT: This study compared warm-up strategies employed by sub-elite and world-class elite sprint kayak athletes, evaluating their impact on subsequent race performance. Forty-seven (n = 33 male, n = 14 female) athletes competing at a National Sprint Kayak Championships had Global Navigation Satellite System devices fitted to their kayak to measure speed, distance and stroke rate during the on-water warm-up before racing (OWWU ), and during racing. The OWWU total duration, average/peak speeds and stroke rates, and the time spent in speed-zones classified based upon athletes' relative race-pace (low-to-moderate, moderate-to-high, and race-specific) were compared between events, sexes, and athlete standard. The relationship of these variables to subsequent race performance, expressed as a percentage of the best time-to-completion for each event (%racebest), was also examined. Women spent greater OWWU time at moderate-to-high and race-specific speeds compared to men prior to 200-m and 500-m races ( P ≤.001). Sub-elite men reported greater total OWWU duration for 200-m and 500-m ( P ≤.025), but not for 1000-m races ( P >.05) compared to elite men. Finally, %racebest had large inverse correlations to OWWU peak speed for men's 200-m (r = −.53), and average stroke rate for women's 500-m races (r = −.50). This study provides valuable insight for competition warm-up routines based upon data from an elite athlete population.